Alcohol mixed with energy drinks: Expectancies of use and alcohol-related negative consequences among a young adult sample. (December 2020) - Powers, Gregory; Berger, Lisa
Highlights: Alcohol mixed with energy drink use is associated with consequences beyond those of alcohol alone. Interpersonal consequences in particular are uniquely associated in this sample. Alcohol mixed with energy drink expectancies play a role in use and consequences. Expectancies may be a target of intervention to reduce alcohol mixed with energy drink use. Abstract: Objective: Energy drinks are a popular mixer with alcohol among college-aged young adults. Few studies to date have examined the relationships between expectancies of alcohol mixed with energy drink (AmED) use, AmED use and AmED-related negative consequences. Methods: Eighty college-aged young adults were surveyed regarding their alcohol and AmED use, related negative consequences and AmED expectancies. Associations were assessed using chi-square tests and Cramér's V. A simple mediational model also was used to explore the potential relationships between AmED expectancies, AmED use and AmED-related negative consequences. Results: AmED use was associated with more types of related negative consequences than heavy alcohol use alone, and where AmED use and heavy alcohol use were mutually associated with a related negative consequence, the strength of association was stronger for AmED use. While several AmED-related negative consequences were associated with AmED expectancies, unwanted sexual contact and getting into a verbal argument were associated with the greatest number of expectancies. The mediational model identified a statistically significant indirect effect of AmED expectancies on AmED-related negative consequences mediated by AmED use. Conclusions: The study results contribute to the evidence that AmED use may confer additional risk for related negative consequences beyond heavy alcohol use and suggest that AmED expectancies may have a role in AmED use, which, in turn, is associated with AmED-related negative consequences. AmED expectancies may be targets for intervention to reduce AmED use considering the possible subsequent related negative consequences, especially those involving negative interpersonal experiences.